Parental and educational perception of mutual responsibility and the influence of certain factors on successful mutual partnership cooperation - Mavračić Miković, Ivana (Array, 2020)
The partnership of educators and parents is in the centre of scientific interest and is one of the fundamental principles of good practice in kindergartens. Often the educators experience such a partnership as stressful in their professional mode of action (Epstein, 2013; Bleach, 2015). This paper seeks to highlight the need to strengthen the professional knowledge and skills of educators to build and develop partnerships with parents. They can be achieved in the course of their professional development, by means of active participation and altering of the existing practices. Therefore, the aim of this research was to examine attitudes and the opinions of parents and educators about their cooperation and partnership. The sample consists of 203 parents and educators from the institutions for early and preschool education from the City of Zagreb and Zagreb County. Hypotheses have been set that are related to the assessment of the importance of cooperation through the participants' own responsibility and also the influence of factors that influence a successful parent educator partnership. Results suggest that respondents highly value mutual collaborative relationships, but do not recognize partnerships as a higher form of cooperation between educators and parents.